A Retrospective Case-Series of Patient-Reported Response to Ultrasound-Guided Corticosteroid Injection of the Long Head of Biceps Tendon in Orthopedic Surgery. (November 2022) - Quintero, Daniel; Singer, Adam; Greif, Dylan N.; Baraga, Michael; Perez, Jose; Jose, Jean
Objective: Identify factors predictive of therapeutic success following ultrasound-guided sheath injection of the long head of the biceps tendon. Materials and Methods: A total of 162 cases were divided into three groups based on clinical responses: complete, partial, or no relief. The presence or absence of clinical symptoms, glenohumeral joint structural pathology, and treatment method was compared. Results: Of the 115 injections with follow-up, 19.1% reported no clinical response while 53.0% had a complete response. Patients with fibromyalgia or chronic spine pain were strongly associated with a poor outcome (odds ratio [OR] = 5.7, P < .001). Conclusion: Ultrasound-guided intra-sheath injection is an effective method of non-surgical management for biceps tendinopathy.